(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
What happens to critical and aesthetic discourse when a painter promises that he will not paint anymore? What goes on when a famous artist says that all the paintings are just junk or dust, and all the institutional sites of the art-world – actually, the White cube of Clement Greemberg’s Modernism – are just wasted spaces? What’s the matter or the reason of the prestige of a similar no-working man, and what’s the perceptible quality of the value of a so-called art without any artefact at all? In the late ’50sand early’60s in Paris, Andy Warhol and Yves Klein claimin different butvery similar ways the end of painting and the disappearing of the work of art from the exposition site and its becoming immaterial or environmental art, indiscernible within its surrounding living space and, finally, with the atmosphere of glamour and snobbish artist’s life. What kind of phenomenology, pragmatic, rhetoric, poetics, economy and ontology is possible when nospectatorialmode of visual consumption is any longer possible? What type of aesthetic relationship actually happens under these planned and produced conditions of non-perceptual and ‘artialized’ living experience? After more than fifty years, the statements of The philosophy of Andy Warhol and the Exposition of void of Yves Klein have not yet stopped to pose questions as such to aesthetics, theory of literature and critics, and to the history of art.